Comparison of macroelement and microelement contents of conventionally and organically grown crops - Fejes, Veronika; Győri, Zoltán; Bardócz, Zsuzsa (Acta Agraria Debreceniensis, 2012)
Nowedays one of the most important issues to discuss is the healthy nutrition: feeding our bodies with high quality nutrients, which is free of chemical residues. The demand for healthy and nutritious food is increasing worldwide, that results in the growing popularity of consumption of organic food. Several studies dealing with the nutrient content of traditional and organic food have been published lately, since it became clear that eating food contaminated with chemical residues damage to health, food and the environment. Therefore it would be desirable to find out if organic food is really superior to conventional one. In our study we analyzed the dry matter, ash, macroelement and trace element content of organically and conventionally grown crops (carrot root, potato tuber and parsnip). Our results provide further information to consumers about the nutritional value of organic and conventional crops.